Theoretical and Islamic Perspective of Leadership - Nawaz, Dawood; Akbar, Muqarrab; Bano, Shehr; Mubarak, Husni (The journal of contemporary issues in business and government, 2021)
An effective leader is someone who must have some universal predestined characteristics i.e.appraising,compassion,communication skills,delegating the authority,emotional quotient, far sightedness, hopefulness, humility,management, passion,problem solver, promising,self- confidence, succession, training, trustworthiness,truthfulness,and so on.The concept of leadership can be approached thorough various points of views including administrative, army, business, community, and from spiritual perspectives. The authors has discussed the leadership concept as analysed through the review of literature about the leadership qualities of our beloved Holy Prophet Hazrat Muhammad (SAW) and his Sahaba (R.A). This study has employed qualitative research technique and it is descriptive in nature and the data has been collected from the Quran, Hadith, books, and research articles. The present researchhas tried to provide an analysis of a leadership theories and religious perspective and also its significance for the peoples who want to become a leader. The leader can lead the people with a vision of accomplishing the common objectives according to the teachings of Islam which are clearly defined in the Holy Quran and the Hadith. Our Holy Prophet Hazrat Muhammad (SAWW) is the role model of the effective leader.